Measurement of the top quark pair cross section with ATLAS in pp collisions at root s=7 TeV using final states with an electron or a muon and a hadronically decaying tau lepton - Onofre, A. (2012)
A measurement of the cross section of top quark pair production in proton–proton collisions recorded with the ATLAS detector at the Large Hadron Collider at a centre-of-mass energy of 7 TeV is reported. The data sample used corresponds to an integrated luminosity of 2.05 fb−1. Events with an isolated electron or muon and a τ lepton decaying hadronically are used. In addition, a large missing transverse momentum and two or more energetic jets are required. At least one of the jets must be identified as originating from a b quark. The measured cross section, View the MathML sourceσtt¯=186±13(stat.)±20(syst.)±7(lumi.) pb, is in good agreement with the Standard Model prediction.